Evaluation of hospital-acquired infections prevention and control programme for nurses in the public hospitals of Limpopo Province - Ranoto, Lebitsi Queen (My University, 2025)
Background: Hospital-acquired infections (HAIs) are a critical global health challenge, posing risks to patient safety and increasing healthcare costs. Infection Prevention and Control (IPC) programs are vital for reducing the incidence of HAIs. However, effective implementation of these programs, particularly in resource-constrained settings, remains a challenge. This study evaluates the implementation of IPC programs in public hospitals in Limpopo Province, South Africa, applying a mixed-methods approach guided by implementation science frameworks. Purpose: The study aims to: (1) conduct a baseline assessment of IPC activities using retrospective data and the Infection Prevention and Control Assessment Framework (IPCAF); (2) explore the attitudes and practices of hospital IPC nurses toward IPC program implementation; and (3) develop an evidence-based strategy to address gaps and improve program outcomes, informed by the WHO Multimodal Strategy. Methodology: This three-phased mixed-methods study began with a quantitative analysis (Phase I) of hospital compliance with IPC standards using the IPCAF tool. Phase II employed qualitative methods to explore nurses’ attitudes and practices through interviews, analysed using the Theoretical Framework of Acceptability (TFA). Thematic analysis highlighted constructs such as perceived effectiveness, burden, ethicality, and self-efficacy. Phase III integrated these findings into a tailored improvement strategy using the WHO Multimodal Strategy to design iterative, sustainable interventions. Furthermore, the results from both phases were integrated and interpreted. Findings: Phase I revealed inconsistencies in IPC compliance, with gaps in resource allocation and program governance. Phase II highlighted critical themes influencing nurse engagement, including ethicality, perceived burden, and affective attitudes. The proposed improvement strategy incorporates the WHO Multimodal Strategy’s core components—system change, training, monitoring, reminders, and institutional safety culture—adapted for the local context. Conclusion: The integration of the WHO Multimodal Strategy with implementation science frameworks provides a robust approach to addressing systemic challenges in IPC program implementation. This study demonstrates the potential for tailored, evidence-based interventions to improve healthcare outcomes in resource-limited settings.
Thesis (Ph.D. (Public Health)) -- University of Limpopo,2025
Keywords: Hospital-acquired infections; Infection prevention and control; WHO Multimodal Strategy; Limpopo Province; Healthcare quality improvement; Implementation research; Mixed-methods study; Nosocomial infections; Cross infection -- Prevention; Hospital care; Health care reform; Nurses -- South Africa -- Limpopo